FACTOR THAT AFFECT STOCK RETURNS OF PROPERTY AND REAL ESTATE SECTOR ON IDX IN 2017-2021 - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine the effect of current ratio, debt to equity ratio, return on investment, earnings per share and dividend payout ratio towards stock returns of property and real estate sector that are listed on the Indonesia Stock Exchange in 2017-2021 period. The sampling technique used was purposive sampling and obtained a sample of 45 companies. The result of this study indicates that the debt to equity ratio has a negative influence on stock returns, while the rest, namely, current ratio, return on investment, earning per share and dividend payout ratio have no effect on stock returns.